The death of Santini [large type] : the story of a father and his son - Conroy, Pat (Random House Large Print, 2013)
A powerful and intimate memoir by the beloved best-selling author of The Prince of Tides about his father, the inspiration for The Great Santini, and a re-affirmation that love can conquer even the meanest of men.